2019
DOI: 10.4067/s0718-07642019000400069
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de Nutrientes de la Raíz de la Malanga (Colocasia esculenta Schott) en el Trópico Seco de Colombia

Abstract: ResumenEl objetivo del estudio fue analizar el contenido de nutrientes de la malanga cultivada en la zona rural del Caribe colombiano. A muestras de malanga se le realizaron análisis proximales, de vitaminas y minerales, con el empleo de los métodos Kjeldahl, Soxhlet, hidrólisis ácido-base, incineración, cromatografía y absorción atómica. Los resultados se compararon con el contenido de nutrientes del camote, la papa, la yuca y el ñame. Los resultados obtenidos fueron 24.99 % de proteínas, 0.53 % de grasa, 59.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
(7 reference statements)
3
8
0
2
Order By: Relevance
“…The RTTF showed moderate content of CP (8.51 %), ash (4.23 %), EE (4.97 %), CF (3.37 %), FDN (22.87 %), FDA (5.36 %), lignin (1.25 %), cellulose (4.10 %) and hemicellulose (17.50 %), respectively (table 2). These results are similar to those reported for taro varieties grown in Africa (Aboubakar et al, 2008;Ndabikunze et al, 2011;Nguimbou et al, 2014), Colombia (Púa et al, 2019), andMexico (Madrigal-Ambriz et al, 2018). Moreover, it has to be noted that taro fiber is considered dietetic and is very advantageous for its active role in regulating the intestinal transit, increasing the diet's volume and stool consistency due to its ability to absorb water (Temesgen & Ratta, 2015).…”
Section: Productive Performancesupporting
confidence: 89%
“…The RTTF showed moderate content of CP (8.51 %), ash (4.23 %), EE (4.97 %), CF (3.37 %), FDN (22.87 %), FDA (5.36 %), lignin (1.25 %), cellulose (4.10 %) and hemicellulose (17.50 %), respectively (table 2). These results are similar to those reported for taro varieties grown in Africa (Aboubakar et al, 2008;Ndabikunze et al, 2011;Nguimbou et al, 2014), Colombia (Púa et al, 2019), andMexico (Madrigal-Ambriz et al, 2018). Moreover, it has to be noted that taro fiber is considered dietetic and is very advantageous for its active role in regulating the intestinal transit, increasing the diet's volume and stool consistency due to its ability to absorb water (Temesgen & Ratta, 2015).…”
Section: Productive Performancesupporting
confidence: 89%
“…Total carbohydrate content was determined by the phenol-sulfuric method according to Polonia-Rivera et al [20] with some modifications where a standard curve was performed with dextrose with a concentration of 0 -140 ppm, reducing sugars were determined according to Amaya-Chantaca et al [21]. The protein content was carried out according to the Lowry spectrophotometric method according to the methodology reported by Redmile-Gordon et al [22] Fiber determination was determined according to that reported by Púa et al [23].…”
Section: Proximate Analysis Of Pineapple Wastementioning
confidence: 99%
“…11 Taro has a high carbohydrate (59.36%) and protein (24.99%) content, the mineral content of Taro, the mineral present in the highest amount is magnesium 242.373 mg/kg, followed by calcium 94.455 mg/kg, iron 8.351 mg/kg and zinc 6.210 mg/kg, and vitamin C 0.188 mg/100 mg, vitamin B1 0.047 mg/100 mg, and Vitamin B3 0.078 mg/100 mg. 12 Compared to other tubers such as sweet potato, potato, cassava and yam; taro has a higher protein and fat content. 12 Likewise, Taro has flavonoids and phenolic acids that have antioxidant properties; flavonoids, the largest group of phenolic compounds identified in the whole plant, are associated with reducing many degenerative diseases. 11 Foodstuffs are complex systems of great nutritional richness and therefore sensitive to attack by microorganisms (bacteria, fungi and yeasts).…”
Section: Introductionmentioning
confidence: 99%